(untitled) (Experimental biology, 2020)
This article generalizes data of authors collected in course of birds count at Lake Cartma Lake Systems of Syrdarya river’s delta of the territory of Kyzylorda region, Republic of Kazakhstan, in period of 2014-2019. Distribution, quantity, ecology and areal of white-tailed lapwing (Vanellochettusia leucura) is considered in details. White-tailed lapwing is a medium-sized wader; body structure largely resembles black-sided lapwing but the size is slightly lesser. At present time, on territory of Kazakhstan, the white-railed lapwing is nesting at wetland stations of middle and downstream (from border with Uzbekistan to North Aral sea), system of lakes in delta of Syr-Darya river, in the north part of Caspian sea. Quantity of white-tailed lawing on studied Cartma lake is determined in limits of 30-150 specimen; this is the result of season nature of countings, fluctuation of area of studied water body surface. A characteristic feature of this species is a peculiar voice, descriptively translated as “chetyre, chetyre” ("four, four” in Russian), increasing at approach to nesting sites. Analysis of special literature on ornithology of eastern site of Aral sea and lakes of Syr-Darya river delta showed that for two hundred years period, white-tailed lapwing mostly adheres to constant habitats. Nesting station is located in shore zone, at sandbars and isles. Key words: Cartma lake, wetlands, white-tailed lapwing, distribution of avifauna, trophic specialization of birds, E.A. Eversmann